2005
DOI: 10.1021/jp0554947
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N−H···O and C−H···O Hydrogen Bonds on the 17O NMR Tensors in Crystalline Uracil:  Computational Study

Abstract: We report a computational study for the 17O NMR tensors (electric field gradient and chemical shielding tensors) in crystalline uracil. We found that N-H...O and C-H...O hydrogen bonds around the uracil molecule in the crystal lattice have quite different influences on the 17O NMR tensors for the two C=O groups. The computed 17O NMR tensors on O4, which is involved in two strong N-H...O hydrogen bonds, show remarkable sensitivity toward the choice of cluster model, whereas the 17O NMR tensors on O2, which is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 36 publications
5
47
0
Order By: Relevance
“…In uracil, O1 contributes to N-H … O type of HB interactions with two neighbor molecules and O2 contributes to C-H … O type of HB interactions with two neighbor molecules. Wu et al [20,21] have recently reported the 17 O NQR parameters of uracil either experimentally or computationally. Because of different HB interaction properties between uracil and 5NU, the calculated NQR parameters of uracil at the same level of calculations are observed in lower fields in comparison with those of 5NU.…”
Section: Comparison Of Results Of This Study With Previous Ones On Urmentioning
confidence: 99%
See 1 more Smart Citation
“…In uracil, O1 contributes to N-H … O type of HB interactions with two neighbor molecules and O2 contributes to C-H … O type of HB interactions with two neighbor molecules. Wu et al [20,21] have recently reported the 17 O NQR parameters of uracil either experimentally or computationally. Because of different HB interaction properties between uracil and 5NU, the calculated NQR parameters of uracil at the same level of calculations are observed in lower fields in comparison with those of 5NU.…”
Section: Comparison Of Results Of This Study With Previous Ones On Urmentioning
confidence: 99%
“…H1 is chemically bonded to N1 and [19,20] for oxygen and from Ref. [21] for nitrogen nuclei. The values in parentheses are calculated at the same level of theory of this study.…”
Section: The 2 H Nqr Parametersmentioning
confidence: 99%
“…However, the positions of hydrogen atoms due to low electron density are not accurately located by x-ray diffraction. Therefore, following the earlier work of Ida et al [26], only the hydrogen positions of peptide group in the single and cluster structures are separately optimized at the level of B3LYP method and 6-311++G** standard basis set while the other atoms positions are kept frozen during the process.…”
Section: Computational Detailsmentioning
confidence: 99%
“…As mentioned above, since NMR tensors are very sensitive to the electrostatic environment of nuclei, such environment must be included in the calculations to have reliable results. A way for this purpose is including the charge points in the calculations; however, two recent studies [18,19] showed that if the target molecule is surrounded by those possible interacting neighbor molecules, the calculated NMR tensors are also reliable. Therefore, trimer forms of NMA were created using coordinates transforming to surround the target molecule by the interacting neighbor ones (see Scheme 1 and Table 1 for details).…”
Section: Introductionmentioning
confidence: 99%